Covered Bonds under Unconventional Monetary Policy - Markmann, Holger (Essays in Real Estate Research,, 2018)
Holger Markmann studies covered bonds and their market behaviour upon the announcement and implementation of outright covered bond purchases by the eurosystem. After introducing the covered bond market, its reaction to the global financial crisis, and the functionality of unconventional monetary policy to a broad audience, the author analyzes the impact of these purchases. The first Covered Bond Purchase Programme (CBPP1) has lowered covered bond spreads by 3-4 basis points in the short-term, 10 basis points in the medium-term, and increased emission volumes by € 103 billion. CBPP2 and CBPP3 have not led to similar effects. However, the programs' effectiveness relies on the market's expectations and its prevalent health. Contents Introduction to Covered Bonds and Unconventional Monetary Policy Impact on Covered Bond Emission Activity Medium- and Short-term Announcement Effects Monetary Policy Implications Target Groups Scientists and students in the fields of monetary policy, banking, finance, and real estate Practitioners in commercial bank treasuries and central bank policy setting About the Author Holger Markmann is PostDoc at the Real Estate Management Institute (REMI) of EBS Universität für Wirtschaft und Recht and Managing Director of a real estate investment firm. His research focuses on real estate capital market financing, bank funding, and unconventional monetary policy. Prior to his current roles, he worked for a bulge bracket investment bank, advising financial institutions on their M&A- and capital market activities.